Methodological Paradigm of Social Interaction as the Basis for Modern Education Resources Research - Sherbakova, Anna Iosifovna; Kamenetz, Alexander Vladlenovich; Anufrieva, Natalya Ivanovna; Anufriev, Evgeniy Aleksandrovich; Zinchenko, Elizaveta Olegovna (International Review of Management and Marketing, 2016)
The article discusses the paradigm of social interaction in the context of its relevance to modern pedagogical research. It identifies the heuristic capabilities of this paradigm for the study of the most topical problems of modern education. It analyses the main pedagogical situations of social interaction that need to be considered when enhancing the teaching effectiveness of the educational process. The authors of the article rely on sociological and anthropological studies in which the situational and interactive approach to the analysis of socio-cultural issues is dominant. The article can be seen as one of possible methodological approaches to the further intensification of pedagogical research of modern education. Keywords: Interaction, pedagogical process, situation, frame, structure, society, communication, modeling. JEL Classifications: Z130, I210, I230